Sex Differences in Plasma Lysophosphatidic Acid Species in Patients with Alcohol and Cocaine Use Disorders - Flores-López, María; García-Marchena, Nuria; Araos Gómez, Pedro Fernando; Requena-Ocaña, Nerea; Porras-Perales, Oscar; Torres-Galván, Sandra; Suárez-Pérez, Juan; Pizarro Lozano, Nieves; De la Torre, Rafael; Rubio, Gabriel; Ruiz-Ruiz, Juan Jesús; Rodriguez-de-Fonseca, Fernando; et al. (IOAP-MPDI, 2022)
Preclinical evidence suggests a main role of lysophosphatidic acid (LPA) signaling in drug addiction. Recently, we reported alterations in the plasma concentrations of LPA species in patients with alcohol use disorder (AUD). As there are sex differences in drug addiction, the main aim of the present study was to investigate whether relevant LPA species (16:0-LPA, 18:0-LPA, 18:1- LPA, 18:2-LPA and 20:4-LPA) were associated with sex and/or substance use disorder (SUD). This exploratory study was conducted in 214 abstinent patients with lifetime SUD, and 91 healthy control subjects. The SUD group was divided according to the diagnosis of AUD and/or cocaine use disorder (CUD). Participants were clinically assessed, and plasma samples were collected to determine LPA species and total LPA. We found that LPA concentrations were significantly affected by sex, and women showed higher concentrations than men. In addition, there were significantly lower 16:0-LPA, 18:2-LPA and total LPA concentrations in patients with SUD than in controls. Namely, patients with CUD and AUD + CUD showed lower LPA concentrations than controls or patients with AUD. In conclusion, our data suggest that LPA species could be potential biomarkers for SUD in women and men, which could contribute to a better stratification of these patients in treatment programs.
Keywords: Drogas; Lysophosphatidic acid; Biomarker; Sex; Substance use disorder; Alcohol; Cocaine